Handbook on foreign direct investment by small and medium-sized enterprises: Lessons from Asia (New York, 1998)
The book contains the results of a questionnaire survey and case studies conducted in selected developing economies in Asia. The survey targeted SMEs that are outward investors in selected home economies, as well as others that are recipients of inward foreign direct investment in selected host countries; the case studies provided further insignts into the experiences of selected host and home countries.
Keywords: investents, asian,investments, foreign